An educational review of cartilage repair: precepts & practice – myths & misconceptions – progress & prospects. Issue 3 (March 2015) - Hunziker, E.B.; Lippuner, K.; Keel, M.J.B.; Shintani, N.
Summary: Objective: The repair of cartilaginous lesions within synovial joints is still an unresolved and weighty clinical problem. Although research activity in this area has been indefatigably sustained, no significant progress has been made during the past decade. The aim of this educational review is to heighten the awareness amongst students and scientists of the basic issues that must be tackled and resolved before we can hope to escape from the whirlpool of stagnation into which we have fallen: cartilage repair redivivus! Design: Articular-cartilage lesions may be induced traumatically (e.g., by sports injuries and occupational accidents) or pathologically during the course of a degenerative disease (e.g., osteoarthritis). This review addresses the biological basis of cartilage repair and surveys current trends in treatment strategies, focussing on those that are most widely adopted by orthopaedic surgeons [viz., abrasive chondroplasty, microfracturing/microdrilling, osteochondral grafting and autologous-chondrocyte implantation (ACI)]. Also described are current research activities in the field of cartilage-tissue engineering, which, as a therapeutic principle, holds more promise for success than any other experimental approach. Results and Conclusions: Tissue engineering aims to reconstitute a tissue both structurally and functionally. This process can be conducted entirely in vitro, initially in vitro and then in vivo ( in situ ), or entirely in vivo . Three key constituents usually form the building blocks of such an approach: a matrix scaffold, cells, and signalling molecules. Of the proposed approaches, none have yet advanced beyond the phase of experimental development to the level of clinical induction. The hurdles that need to be surmounted for ultimate success are discussed.